2002
DOI: 10.1212/wnl.58.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Tau protein and 14-3-3 protein in the differential diagnosis of Creutzfeldt–Jakob disease

Abstract: The differential diagnostic significance of the 14-3-3 immunoblot is similar to that of the tau-protein ELISA. The advantage of the tau-protein ELISA is that it is easy to use in routine laboratories. Patients with a negative 14-3-3 immunoblot already have measurable tau-protein levels. This increases information on 14-3-3-negative patients with CJD and especially on patients with other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
198
3
25

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(245 citation statements)
references
References 46 publications
19
198
3
25
Order By: Relevance
“…In agreement with earlier studies, we found excessively high levels of t-tau in CJD patients compared to the AD and the age-matched HC groups [15,20,21]. CSF p-tau 231 concentrations, however, were significantly lower in CJD patients compared to the AD group, indicating an opposite direction of change in t-tau and p-tau 231 expression in the CSF of CJD patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with earlier studies, we found excessively high levels of t-tau in CJD patients compared to the AD and the age-matched HC groups [15,20,21]. CSF p-tau 231 concentrations, however, were significantly lower in CJD patients compared to the AD group, indicating an opposite direction of change in t-tau and p-tau 231 expression in the CSF of CJD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Each patient was visited by a research physician and examined using a standardized protocol. According to the clinical criteria, all suspected cases of CJD were classified as "probable", "possible", or "other" cases [15]. Before clinical staging into "probable" or "possible", all patients underwent at least one cranial CT or MRI, or both, to exclude ischemic stroke, hemorrhage, or space-occupying lesions as a cause of the illness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar punctures were performed at time of diagnosis; CSF tau protein levels were quantitatively analysed using a commercially available ELISA according to the manufacturer's instructions (Innogenetics, Ghent, Belgium) (Otto, et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…CSF Tau protein was quantitatively analysed using a commercially available ELISA according to the manufacturer's instructions (Innogenetics, Ghent, Belgium). A positive Tau-test was considered at a cut off level >1300pg/ml [10].…”
Section: Csf Analysesmentioning
confidence: 99%